Roxtec seals play important role in infrastructure overhaul at UK nuclear waste site. Issue 10 (October 2019) - Atkinson, Simon
Abstract : Roxtec UK – the British subsidiary of Sweden's Roxtec Group, a provider of modular-based cable and pipe seals – is supplying cable sealing systems to support a major project that involves the overhaul of infrastructure at Sellafield, Britain's largest nuclear waste site. This brief technology focus illustrates the benefits of using the company's technology and describes how it is being applied.